Integrating design thinking into dental education - Chuenjitwongsa, Supachai; Amir, Lisa R.; Jessani, Abbas; Samaranayake, Lakshman P.; Osathanon, Thanaphum (Frontiers in Oral Health, 2025)
Design thinking is a human-centred, iterative process that aims to develop innovative solutions tailored to user needs. This article examines the groundwork and incorporation of design thinking in healthcare and medical education, highlighting its potential benefits in dental education, including enhancements in learner-centred approaches, faculty development, interprofessional collaboration, and person-centred care. Design thinking methods foster learner engagement, aligning with cognitive and constructivist learning theories. Active engagement and discourse among learners create meaningful learning experiences, benefiting from a “learning by doing” approach. Further, design thinking processes ensure critical thinking and collaborative learning, supporting active engagement with prior knowledge and constructive feedback skills. Thus, applying design thinking in dental education could deepen learners' understanding with improved problem-solving skills, ultimately leading to effective learning outcomes.